A Feasibilty Study on the Establishment of Bellissima Makeup Studio in 6114 El Grande Gen. T. De Leon, Valenzuela City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Bellissima Makeup Studio offers hair and makeup services such as on the spot service and home service for various occasions including wedding, debut, pageant and other event. The business will be located at 6114 El Grande Gen T. De Leon, Valenzuela City. Also, the company offers hair and makeup tutorial that will help the customer to advance their knowledge and skills for doing hair and makeup. Company’s promotional strategies includes print advertisement and use of social media. Thus, the company service offering will help to boost the customers’ self-esteem as they show their beauty. The researchers conducted a survey to 100 randomly selected respondents using a questionnaire which includes the profile of respondents with 12 questions including checklist, multiple choice and yes or no questions. This was in order to know their needs and wants in terms of service, price, place and promotion and to be able to know if the business would be feasible. The survey was conducted at El Grande Gen T De Leon Valenzuela City. Based on the survey, 85% of the respondents agreed to avail of hair and makeup services and 80% preferred makeup packages for special occasions. 79% of the respondents were interested in availing on the spot hair and makeup service. The survey alsoshows that 85% of the respondents want to avail hair and makeup tutorial sessions. In availing service, 75% of the respondents agreed to book online via Facebook, 12% answered phone call while 10% answered walk in. The survey shows that the 48% of respondents prefer makeup brush as freebies for promotional materials, 29% for T-Shirt, 14% for keychain and 9% for tumbler.
Keywords: feasibility study, make up studio, hair and make-up, make up tutorial